2011
DOI: 10.1002/ima.20278
|View full text |Cite
|
Sign up to set email alerts
|

Beyond topographic representation: Decoding visuospatial attention from local activity patterns in the human frontal cortex

Abstract: The ability to detect where a person is attending is fundamental for brain-computer-interfaces. We explore how the attentional focus can be decoded from brain signals noninvasively acquired with functional magnetic resonance imaging (fMRI). Several cortical regions have previously been reported to have topographic maps reflecting the focus of visual attention. Interestingly, attentional maps were observed to be gradually less topographic when moving from early visual areas toward extra-occipital areas. Recent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 72 publications
1
7
0
Order By: Relevance
“…Consistent with this, PPC is believed to be involved in encoding of attention and saliency processing (Bisley and Goldberg, 2006;Bogler et al, 2011). It has been shown that PPC contains a retinotopic representation of the contralateral visual field (Sereno et al, 2001) and even that it has information about spatial attention in the ipsilateral visual field (Kalberlah et al, 2011). Our findings suggest that these contralateral and ipsilateral representations of visual space may also be capable of representing visual working memory content.…”
Section: Discussionsupporting
confidence: 85%
“…Consistent with this, PPC is believed to be involved in encoding of attention and saliency processing (Bisley and Goldberg, 2006;Bogler et al, 2011). It has been shown that PPC contains a retinotopic representation of the contralateral visual field (Sereno et al, 2001) and even that it has information about spatial attention in the ipsilateral visual field (Kalberlah et al, 2011). Our findings suggest that these contralateral and ipsilateral representations of visual space may also be capable of representing visual working memory content.…”
Section: Discussionsupporting
confidence: 85%
“…In one study, radial and concentric patterns had been associated with differential button presses during training, although during scanning, participants performed an unrelated task (Mayhew et al, 2010). In all other cases, any button press responses given by participants were orthogonal (Mayhew & Kourtzi, 2013) or unrelated (Pollmann et al, 2014;Reverberi et al, 2012a;Kalberlah et al, 2011;Mayhew et al, 2010) to the visual discrimination.…”
Section: Discussionmentioning
confidence: 99%
“…We excluded any papers in which there were obvious associations between our task features, and in our stricter analysis, we also excluded any studies in which higher-level features such as semantic category differed between decoded items, or cases where items might evoke representations of associated motor actions. The remaining points of visual discrimination in the motor cortex were for discrimination between Gabor patches differing in color and spatial frequency (Pollmann, Zinke, Baumgartner, Geringswald, & Hanke, 2014), the spatial location of a target (Kalberlah, Chen, Heinzle, & Haynes, 2011), radial versus concentric glass patterns (Mayhew & Kourtzi, 2013;Mayhew, Li, Storrar, Tsvetanov, & Kourtzi, 2010), and between two abstract shapes cuing the same rule (Reverberi, Gorgen, & Haynes, 2012a). In one study, radial and concentric patterns had been associated with differential button presses during training, although during scanning, participants performed an unrelated task (Mayhew et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Instead, we would be able to identify even spatially anisotropic distributions of cells that code for specific attended subregions of the visual field. In an fM-RI study [20], participants shifted their visuospatial attention toward cued targets (. Fig.…”
Section: Non-topographic Representations Of Visual Spatial Attention mentioning
confidence: 99%
“…7a). MVPA techniques revealed that, a few seconds before [20] and [10] the decision was consciously made, highlevel control regions including lateral and medial frontopolar cortex, and precuneus/posterior cingulate, already began to encode the content of the upcoming decision in their local spatial patterns of activity, despite showing no overall increase in fMRI signal (. Fig.…”
Section: Decoding Perceptual Decisions and Perceptual Guessingmentioning
confidence: 99%